Health behaviours in severely obese women prior to conception and during pregnancy. (7th June 2011) - Duthie, L B; Mohd-shukri, N; Forbes, S; Dennison, F; Norman, J; Reynolds, R
Abstract : Background: Recent guidelines from National Institute for Health and Clinical Excellence emphasise health reinforcement in the periconceptual period. This places pressure to identify women prior to conception to advise on health behaviours, particularly smoking, alcohol consumption and folic acid. Pregnancies in obese women are associated with higher maternal and fetal complication rates but it is unknown whether health behaviours of obese women prior to and during pregnancy differ from non-obese women. Objective: To assess health behaviours pre-conception and during pregnancy in severely obese women. Methods: 164 obese (body mass index (BMI)≥40) and 53 normal-weight (BMI<25) pregnant women attending an antenatal metabolic clinic completed questionnaires concerning health behaviours. Results: Obese women were significantly less likely to have taken folic acid prior to conception compared with controls (26.6% vs 58.3% p<0.0001). Obese women were more likely to smoke at time of conception (obese 21.4% vs control 8.5% p=0.046). There was no difference between obese or lean women in those who continued to smoke during pregnancy (61.8% vs 50% p=0.65). Obese women were more likely to consume alcohol within recommended limits prior to conception (57.7% vs 29.8%, p<0.0001). Social class differed between groups with higher deprivation scores among the obese group (4.3 (0.11) vs 3.1 (0.18), p<0.0001). Differences in health behaviours remained significant after adjustment for social class. Conclusion: Our data suggest that severely obese women planning pregnancy comply poorly with lifestyle recommendations. Greater education regarding smoking, alcohol and folic acid intake among women of child-bearing age is required, particularly among this high risk obese group.